1994
DOI: 10.1177/096120339400300505
|View full text |Cite
|
Sign up to set email alerts
|

HLA Antigens in Malay Patients with Systemic Lupus Erythematosus

Abstract: Many studies have shown an association between human leucocyte antigens (HLA) and systemic lupus erythematosus (SLE) in the various study populations. Although SLE is not an uncommon disease in the Malaysian Archipelago, and appears to affect all three major racial groups equally (i.e. Southern Chinese, Malays and Southern Indians), very little information is available on the HLA profiles in the two latter groups. In phase I of our study of the HLA profiles in Malaysian SLE patients, the HLA phenotypes (class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…HLA-C alleles, the ligands of KIR2D genes, are highly polymorphic; these loci segregate to KIR genes, and NK cells can express KIRs for which there is no known HLA ligand present. In this study, we showed that HLA-Cw*07 was present more frequently in SLE patients than in healthy subjects, which is consistent with the findings reported by Kong et al [28]. HLA-C is the classic HLA-I gene, which was on the short arm of human chromosome 6, between HLA-A and B.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…HLA-C alleles, the ligands of KIR2D genes, are highly polymorphic; these loci segregate to KIR genes, and NK cells can express KIRs for which there is no known HLA ligand present. In this study, we showed that HLA-Cw*07 was present more frequently in SLE patients than in healthy subjects, which is consistent with the findings reported by Kong et al [28]. HLA-C is the classic HLA-I gene, which was on the short arm of human chromosome 6, between HLA-A and B.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we showed that HLA‐Cw*07 was present more frequently in SLE patients than in healthy subjects, which is consistent with the findings reported by Kong et al . . HLA‐C is the classic HLA‐I gene, which was on the short arm of human chromosome 6, between HLA‐A and B.…”
Section: Discussionmentioning
confidence: 99%
“…In Caucasian populations, this allele frequency was significantly increased in Bulgarian and Russian populations [17]. In the two previous studies in Malay SLE patients, only one of them looked at HLA-A1 but found no association [9]. A previous study in Hong Kong SLE patients also showed no association of SLE with HLA-A alleles [18].…”
Section: Discussionmentioning
confidence: 92%
“…The only three previous publications on HLA associations in Malay [9,10] and Chinese [11] Malaysian SLE patients examined a small number of HLA loci. His study was aimed at examining a fuller set of HLA loci associations in a population of Malay and Chinese SLE patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some were found to bear DR‐7, for example, 5 while others did not express either DR‐2 or DR‐3 6 . The HLA–DR‐2 or its split, predominantly DR‐15, were more common in some Caucasians, 1 Asians, 7 African Americans 8 and South African Black patients 9 …”
Section: Frequency Of Hla‐dr In Patients With Sle and In Healthy Conmentioning
confidence: 99%